Respuesta :
3x + y = 4....multiply by -1
2x + y = 5
--------------
-3x - y = -4 (result of multiplying by -1)
2x + y = 5
--------------add
-x = 1
x = -1
2x + y = 5
2(-1) + y = 5
-2 + y = 5
y = 5 + 2
y = 7
solution is (-1,7)
2x + y = 5
--------------
-3x - y = -4 (result of multiplying by -1)
2x + y = 5
--------------add
-x = 1
x = -1
2x + y = 5
2(-1) + y = 5
-2 + y = 5
y = 5 + 2
y = 7
solution is (-1,7)
3x + y = 4
2x + y = 5
-3x - y = -4
2x + y = 5
-x = 1
x = -1
2x + y = 5
2(-1) + y = 5
-2 + y = 5
y = 5 + 2
y = 7
solution is (-1,7) hope this helps
2x + y = 5
-3x - y = -4
2x + y = 5
-x = 1
x = -1
2x + y = 5
2(-1) + y = 5
-2 + y = 5
y = 5 + 2
y = 7
solution is (-1,7) hope this helps